Representasi Ieseido pada Manga Watashi no Shiawase na Kekkon Karya KÅsaka Rito dan Agitogi Akumi - Noor Intan Kemala Agusnie; Puspa Mirani Kadir; Budi Rukhyana (Universitas Airlangga, 2024)
家制度/ Ieseido is a Japanese family system that emerged and grew in the Edo period and ended in the Showa period. Ieseido lasted from the Edo period to the Showa period, so it is often represented in the manga, one of which is found in a manga set in the Meiji to Showa period entitled Watashi no Shiawase na Kekkon (Watakon) by Kōsaka Rito and Agitogi Akumi. This article uses a descriptive qualitative method with Stuart Hall’s representation theory. The results show that there is a representation of the concept of Ieseido in the Watakon manga. Traditional Japanese values related to the concept of Ieseido, such as loyalty to family, social hierarchy, and gender roles are explicitly shown in the manga panels. The analysis also shows the importance of understanding representation not only as a passive reflection of reality but also as an active construction that impacts how identity and social relations are perceived.